Physical functioning and physical activity after gastrointestinal or bladder oncological surgery: An observational cohort study. (17th October 2022) - Bor, Petra; de Leeuwerk, Marijke Elizabeth; Valkenet, Karin; van Hillegersberg, Richard; Veenhof, Cindy
Abstract: Objective: The aim of this study was to investigate the recovery of physical functioning and objective physical activity levels up to 3 months after oncological surgery and to determine the association between physical activity levels and the recovery of physical functioning. Methods: A longditudinal observational cohort study was conducted in patients who underwent gastrointestinal or bladder oncological surgery. Recovery of physical functioning was measured preoperatively, and 1 and 3 months after discharge. Physical activity was objectively measured with an accelerometer during hospitalisation, and 1 and 3 months after discharge. Results: Between February and November 2019, 68 patients were included. Half of the patients (49%) were not recovered in physical functioning 3 months after surgery. During hospitalisation, physical activity increased from 13 to 46 median active minutes per day. At 1 and 3 months after discharge, patients were physically active for 138 and 159 median minutes per day, respectively. Patients with higher levels of physical activity 1 month after discharge showed to have higher levels of physical functioning up to 3 months after discharge. Conclusion: At 3 months after surgery, physical functioning is still diminished in half of the patients. It is important to evaluate both physical activity levels and physical functioning levels after surgery to enable tailored postoperative mobility care.